Dedifferentiation and difference: People with profound intellectual and multiple disabilities and the National Disability Insurance Scheme (NDIS). Issue 4 (1st October 2020) - King, Michelle
ABSTRACT: Dedifferentiation represents the merging of the wider "intellectual disability" category with the broader one of "disability" generally; a product of the ascendance of the social model of disability. The recent re-emergence of the significance of impairment and embodiment in disability theory re-establishes the importance of situated experience and reinserts realities of difference in the dedifferentiation/difference debate. This paper highlights these issues by exploring the experiences of people with Profound Intellectual and Multiple Disabilities (PIMD) and their decision-making supporters in the context of the National Disability Insurance Scheme (NDIS) in Australia. Lived experiences accessing, planning for, and implementing NDIS supports illustrate some limitations of dedifferentiation in social services, highlighting the need for recognition of realities of embodied difference for people with PIMD. Here, our systems and theories are most uncomfortable, our ideals of inclusion are most challenged in practice, and some balance between realities of difference and ideals of dedifferentiation is most needed.